Financial Development and Poverty Reduction in Indonesia: An Empirical Investigation - Vita Kartika Sari (Universitas Negeri Semarang, 2025)
Poverty in Indonesia has decreased but still presents many challenges in achieving significant reduction targets. The main objective of this study is to estimate the effect of financial sector development on poverty in Indonesia. The dependent variable was household final consumption expenditure as a proxy for poverty, while the independent variables were broad money and gross savings. The study used time series data and applied the ARDL-ECM (Autoregressive Distributed Lag–Error Correction Model) method for 1981–2022. The main finding was that broad money did not significantly affect poverty reduction. Gross savings were significant with a negative coefficient; higher savings were associated with higher poverty rates due to decreased consumption. Furthermore, the stability of the research model was tested using normality, serial correlation, heteroscedasticity, cumulative sum (CUSUM), and cumulative sum of squares (CUSUMQ) tests. The financial sector can reduce poverty through efficient financial services for the poor, microeconomic empowerment, and increased financial inclusion. In the future, the government must promote a conducive and competitive financial sector to support poverty alleviation programs